IGFBP-2 Signaling in the Brain: From Brain Development to Higher Order Brain Functions - Khan, Shumsuzzaman (Frontiers in Endocrinology, 2019)
Insulin-like growth factor-binding protein-2 (IGFBP-2) is a pleiotropic polypeptide that functions as autocrine and/or paracrine growth factors. IGFBP-2 is the most abundant of the IGFBPs in the cerebrospinal fluid (CSF), and developing brain showed the highest expression of IGFBP-2. IGFBP-2 expressed in the hippocampus, cortex, olfactory lobes, cerebellum, and amygdala. IGFBP-2 mRNA expression is seen in meninges, blood vessels, and in small cell-body neurons (interneurons) and astrocytes. The expression pattern of IGFBP-2 is often developmentally regulated and cell-specific. Biological activities of IGFBP-2 which are independent of their abilities to bind to insulin-like growth factors (IGFs) are mediated by the heparin binding domain (HBD). To execute IGF-independent functions, some IGFBPs have shown to bind with their putative receptors or to translocate inside the cells. Thus IGFBP-2 functions can be mediated both via insulin-like growth factor receptor-1 (IGF-IR) and independent of IGF-Rs. In this review, I suggest that IGFBP-2 is not only involved in the growth, development of the brain but also with the regulation of neuronal plasticity to modulate high-level cognitive operations such as spatial learning and memory and information processing. Hence, IGFBP-2 serves as a neurotrophic factor which acts via metaplastic signaling from embryonic to adult stages.